Sources of Acquisition and Changes in IT Staff Competence on the Example of Manufacturing Companies Implementing Cloud Computing Solutions in Poland - Anna PAMULA (Communications of International Proceedings, 2021)
The participation of IT staff in creating business strategies consists not only in determining the technology, but above all in defining the competencies and ensuring efficiency and continuity in the provision of IT services. This paper aimed to increase knowledge on the process around transforming and getting required IT skills while cloud computing adoption in Polish manufacturing companies. The main methodology applied was devoted to the data collected by the means of a quantitative research. For the purpose of the study the questionnaire was developed on the basis of desk research analysis. The data were gathered using CATI method in 2018 and 2020. The results of the research lead to the conclusion that the way companies address the IT staff skills may vary in time. It also showed some general trends in changes in the competences of the IT staff and the methods of acquiring them. The results for the year 2018 showed that the set of skills related to Data Privacy and Security was pointed out as the area of tremendous changes, while in the 2020 more diverse set of the most frequently acquired skills was observed: in case of micro and small companies the highest increase in the Customer Service competencies was indicated, in case of medium companies skills regarding Application Integration were on top. All investigated companies acquired more new competencies in 2020 comparing to 2018 and Training was the most popular method of the acquisition.
Keywords: Digital Transformation; Cloud Computing; Manufacturing; Digital Skills.